The Portrayal of Women Characters in the Novel Well-Behaved Indian Women by Saumya Dave: The Study of Gynocriticism - Miftahur Roifah (Jurnal Bahasa, Sastra, dan Studi Amerika, 2023)
The objective of this research was to examine how women characters are depicted in Saumya Dave's novel, Well-Behaved Indian Women, using four models of Gynocriticism proposed by Elaine Showalter. The research employed a descriptive qualitative methodology, relying on data in the form of descriptions and dialogues from the novel. The data gathered through reading the novel and relevant references, was analyzed by organizing, managing, and interpreting it using the chosen theoretical framework. The findings revealed that Dave's novel incorporates the four models of Gynocriticism, namely women's writing and woman's body, women's writing and women's language, women's writing and woman's psyche, and women's writing and women's culture, in its portrayal of the women characters.